Histology and ultrastructure of the fat body of Anticarsia gemmatalis (HÜBNER, 1818) (LEPIDOPTERA: NOCTUIDAE) - Carvalho,Renata Baldo Rodrigues (2013)
The aim of this study was to analyze the morphologically the fatty body of fourth-instar Anticarsia gemmatalis larvae under light, transmission and scanning electron microscopy. Two distinct portions of the fat body were detected: the parietal (PA) and perivisceral (PV). The PA, the parietal portion, presented a long-stripped shape located below the tegument and lateral to the digestive tube. The PV, rarely observed, was in dorsal region, adhered to digestive wall. Both the portions were constituted of only one cellular type, the trophocytes. These cells in the PA were organized in one layer of thickness showing cylindrical contiguously morphology, whereas the PV was comprised by a mass of small cells, superposed as clusters. Both the portions were covered by a layer of connective tissue, grouping the trophocytes and keeping them separated from the hemolymph. The cytoplasm of the trophocytes from the PA presented acidophilic stain, while the basophilic cytoplasmic of the trophocytes from the PV was due to the large amount of rough endoplasmic reticulum. From the results, it could be concluded that the fat body presented morphological and ultrastructural differences according to the portion and that these features could characterize distinct functions.